PENGARUH KOMITMEN ORGANISASI, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP INTENSI TURNOVER PEGAWAI PADA DINAS PERIKANAN KOTA TANJUNGBALAI - Mahnim Pane; Poltak Parluhutan Simarmata; Nufrizal . (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study is: How is the influence of organizational commitment, work environment and job satisfaction on employee turnover  intentions  at Dinas  Perikanan  Kota  Tanjungbalai.  This  study  aims  to determine  the effect of organizational  commitment,  work environment  and job satisfaction on employee turnover intentions. With total sampling technique, the sample   in  this  study   was  41  people.   The  results   showed;   Organizational commitment  partially  has a positive  effect on employee  turnover  intentions   of 3.882;  The  work  environment  partially  has  a  positive  influence  on  employee turnover  intentions  of 2,988;  Job satisfaction  partially  has a positive  effect  on employee turnover intentions of 2.646; Organizational commitment, work environment  and job satisfaction simultaneously  have a positive and significant effect on employee turnover intentions of 24,881.